Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ijcha.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Acute contractile recovery extent during biventricular pacing is not associated with follow-up in patients undergoing resynchronization

Abstract: BackgroundIt has been reported that contractility, as assessed using dobutamine infusion, is independently associated with reverse remodeling after CRT. Controversy, however, exists about the capacity of this approach to predict a long-term clinical response. This study's purpose was to assess whether long-term CRT clinical effects can be predicted according to acute inotropic response induced by biventricular stimulation (CRT on), as compared with AAI–VVI right stimulation pacing mode (CRT off), quantified at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In accordance with these findings, MPP responders in our study also showed a significant acute improvement in LVEF and |GLPS| as well as a significant acute reduction in mechanical dispersion during MPP pacing configuration, whereas long‐term nonresponders did not. However, DeVecchi et al found that acute contractile recovery in CRT patients was not associated with 3 years prognosis. Bogaard et al also demonstrated that the acute improvement in LV dP/dt(max) was not correlated to clinical outcome (eg, 1‐year survival free from all‐cause mortality, heart transplantation, or LV assist device implantation).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In accordance with these findings, MPP responders in our study also showed a significant acute improvement in LVEF and |GLPS| as well as a significant acute reduction in mechanical dispersion during MPP pacing configuration, whereas long‐term nonresponders did not. However, DeVecchi et al found that acute contractile recovery in CRT patients was not associated with 3 years prognosis. Bogaard et al also demonstrated that the acute improvement in LV dP/dt(max) was not correlated to clinical outcome (eg, 1‐year survival free from all‐cause mortality, heart transplantation, or LV assist device implantation).…”
Section: Discussionmentioning
confidence: 98%
“…In accordance with these findings, MPP responders in our study also showed a significant acute improvement in LVEF and |GLPS| as well as a significant acute reduction in mechanical dispersion during MPP pacing configuration, whereas long-term nonresponders did not. However, DeVecchi et al 18…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Patients' prognosis, however, may be insufficient in predicting CRT responsiveness, as documented by DeVecchi et al with respect to contractile recovery in patients following CRT. 23 In the current study, we investigated the possibility of using STE as a prediction tool for successful CRT implantation treatment. We were able to image patients immediately after the implantation, documenting cardiac function using all types of pacing prior to any remodelling achieved by the CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials on CRT did not investigate whether an acute improvement in contractility as measured by systolic blood pressure can predict long-term outcome. A non-randomized study by deVecchi et al that included 96 patients with systolic heart failure and CRT demonstrated that acute contractile improvement under biventricular versus RV pacing is not associated with 3 years prognosis [16].…”
Section: Discussionmentioning
confidence: 99%